Emphysema and extrapulmonary tissue loss in COPD: a multi-organ loss of tissue phenotype. Issue 2 (8th February 2018) - Celli, Bartolome R.; Locantore, Nicholas; Tal-Singer, Ruth; Riley, John; Miller, Bruce; Vestbo, Jørgen; Yates, Julie C.; Silverman, Edwin K.; Owen, Caroline A.; Divo, Miguel; Pinto-Plata, Victor; Wouters, Emiel F.M.; et al.
We tested whether emphysema progression accompanies enhanced tissue loss in other body compartments in 1817 patients from the ECLIPSE chronic obstructive pulmonary disease (COPD) cohort. Clinical and selected systemic biomarker measurements were compared in subjects grouped by quantitative tomography scan emphysema quartiles using the percentage of low attenuation area (LAA%). Lowest and highest quartile patients had amino-acid metabolomic profiles. We related LAA% to 3 years decline in lung function (forced expiratory volume in 1 s (FEV1 )), body mass index (BMI), fat-free mass index (FFMI) and exacerbations, hospitalisations and mortality rates. Participants with more baseline emphysema had lower FEV1, BMI and FFMI, worse functional capacity, and less cardiovascular disease but more osteoporosis. Systemic C-reactive protein and interleukin-6 levels were similar among groups, but club cell protein 16 was higher and interleukin-8, surfactant protein D and soluble receptor for advanced glycation end product were lower with more emphysema. Metabolomics differed between extreme emphysema quartiles. Patients with more emphysema had accelerated FEV1, BMI and FFMI decline and more exacerbations, hospitalisations and mortality. COPD patients with more emphysema undergo excessive loss of pulmonary and extrapulmonary tissue, which is probably related to abnormal tissue maintenance. Because of worse clinical outcomes, we propose this subgroup be named the multi-organ loss of tissue (MOLT) COPD phenotype. COPD patients with more severe emphysema lose excessive pulmonary and extrapulmonary tissue http://ow.ly/rbnw30hFwEt